2023
DOI: 10.3389/fendo.2023.1167546
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation enzymes in the kidneys of male and female BTBR ob/ob mice

Abstract: Diabetic kidney disease (DKD) is the leading cause of the end-stage renal disease. Recent studies have shown that epigenetic modifications contribute to alterations in gene expression and the development of DKD. This study aimed to show an expression profile of key DNA (de)methylation enzymes (DNMT, TET proteins) and their differences between sexes under obesity and diabetic condition. Male and female black and tan brachyury (BTBR) ob/ob mice and their corresponding wild-type littermates (BTBR WT) were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Recent studies in complex diseases reveal the close relationship between sex hormones and epigenetic modifications, i.e., changes in gene expression patterns that are not directly related to the alteration of the DNA sequence itself [186,187]. Studies on epigenetic alterations in a mouse model of DKD have shown a sexual dimorphism in the expression of key (de)methylation enzymes [188], suggesting a possible link to differences in sex hormone expression between males and females. In CD4+ T cells from SLE patients, estradiol treatment inhibited DNA methyltransferase 1, causing global DNA hypomethylation [189].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in complex diseases reveal the close relationship between sex hormones and epigenetic modifications, i.e., changes in gene expression patterns that are not directly related to the alteration of the DNA sequence itself [186,187]. Studies on epigenetic alterations in a mouse model of DKD have shown a sexual dimorphism in the expression of key (de)methylation enzymes [188], suggesting a possible link to differences in sex hormone expression between males and females. In CD4+ T cells from SLE patients, estradiol treatment inhibited DNA methyltransferase 1, causing global DNA hypomethylation [189].…”
Section: Discussionmentioning
confidence: 99%
“…Advanced diabetes patients commonly experience a range of complications, increasing the complexity of treatment. Compared with normal mice, obese/diabetic mice show different expression patterns of DNMTs and TET proteins in their kidney tissues, which may promote the progression of diabetic nephropathy by regulating DNAm levels 79 . Ten‐eleven translocation methylcytosine dioxygenase 2 (TET2) can demethylate the CGI of transforming growth factor β1 (TGFB1) to promote glomerulosclerosis and accelerating the progression of diabetic nephropathy 80 .…”
Section: Dnam In Obesity‐associated Diseasesmentioning
confidence: 99%